Kebijakan Desentralisasi Fiskal, Pergeseran Sektoral, dan Ketimpangan Antarkabupaten/Kota di Sulawesi Tengah - Arham, Muhammad Amir (UI Scholars Hub, 2014)
Fiscal decentralization can create efficiency and effectiveness to promote growth and change in economic structures as well as to reduce inequalities amongst regions. This study intends to find out whether the fiscal decentralization policies during 2001-2010 contribute to the shift of economic sectors and inequality rates amongst districts/municipalities in the Province of Central Sulawesi. By using econometrics of panel data, the study found that fiscal decentralization supports a shift in the economic sector where the role of primary sector gradually decreased and the secondary and tertiary sector tend to be increased since the implementation of regional autonomy. As a result, the fiscal decentralization creates an economic change in Central Sulawesi, while at the same time, can inevitably generates higher economic inequality amongst regencies/municipalities in the region.